Genetic diversity of Passiflora setacea in different regions of Bahia, Brazil, through SSR markers - Barbosa, Naíra Costa Soares; Leite, Kelly Regina Batista; Carvalho, Maria Luiza Silveira de; Barbosa, Cristiane de Jesus; Schnadelbach, Alessandra Selbach (Comunicata Scientiae, 2021)
Passiflora setacea DC. is a wild species of passion fruit popularly known as ‘maracujá-do-sono’ or ‘sururuca’. It has been recognized for its potential in passion fruit genetic improvement, due to its resistance to several phytopathogens. The purpose of this study was to evaluate the genetic diversity among and within wild populations of P. setacea DC. from different regions of Bahia state, Brazil, revealed by SSR markers. In this regard, 147 samples of plants were collected from 18 localities and six different identity territories in the state. Six pairs of primers were able to amplify polymorphic loci for all individuals. We performed principal coordinates analysis (PCoA) and molecular variance analysis (AMOVA) using Nei genetic distances between individuals of each locations. In addition, we performed two Bayesian analyzes, using Structure and Structurama softwares. High levels of genetic differentiation between populations were observed, as well as the absence of correlation between genetic and geographic distances using the Mantel test. The populations have moderate polymorphism and diverge into two groups: one including populations from the southwestern distribution range, while the other contains all other populations. The existence of two genetic groups was supported by both Bayesian analyses of genetic structure. These results indicate that these populations should be considered for conserving the diversity of P. setacea in germplasm banks, as well as the use in genetic improvement programs of passion fruit.